Gaya Kepemimpinan Transformasional Dan Komunikasi Persuasif Dalam Meningkatkan Budaya Mutu Sekolah - Mohammad Zaki Zamzami (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2023)
This research aims to reveal the leadership style applied in an educational institution combined with persuasive communication in improving the culture of educational quality. Some of the objectives of this research are: 1) To observe the transformational leadership style of the principal. 2) To understand the persuasive communication of the principal. 3) To describe improving the school's quality culture through the transformational leadership style and persuasive communication of the principal. The research method used is a descriptive research method with a qualitative approach. Data collection was carried out by observation, interviews and documentation to obtain information about the problem being studied. Meanwhile, data analysis carried out data reduction for data presentation and data leverage by drawing conclusions from the description. The research results are described in three aspects. First, the implementation of the school principal's leadership style in improving the culture of educational quality. Second, an effective school principal's persuasive communication is based on the character of each teacher and stakeholder. Third, improving school quality culture through transformational leadership style and persuasive communication by school principals in formulating vision and mission